An influence of sensorimotor coordination at the technical preparedness of young athletes in rhythmic gymnastics - Alla Mullagіldіna (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to reveal the influence of the level of development of sensorimotor coordination of gymnasts 8-9 years on technical preparedness in exercise with clubs. Material & Methods: tested ten gymnasts for 8-9 years on eleven test exercises with clubs, revealed the level of differentiation of muscular effort and reproduction of the time interval, statistical and correlation analysis of the data was carried out. Results: close correlation relations of the marks for the performance of the competitive exercise with clubs are revealed with accuracy of reproduction of the time interval (r=0,7); heteronymic circles: in front - a large facial, behind the head - medium (r=0,7); with catching the clubs in two hands on the jump "touching" after throwing the left (r=0,7). Conclusion: to perform basic exercises with clubs gymnasts affect the ability to analyze spatial-temporal characteristics of motions, differentiation own muscular effort proprioceptive sensitivity and anticipation.